2005
DOI: 10.1080/17290376.2005.9724842
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol abuse, gender-based violence and HIV/AIDS in Botswana: establishing the link based on empirical evidence

Abstract: The existence of gender-based violence has been a source of concern within the public and private sectors as well as civil society organisations in Botswana. The present study investigated the link between alcohol abuse, gender-based violence and HIV/AIDS. Further, it attempted to unravel the often unquestioned assumption that gender-based violence is perpetuated by cultural practices. Case study qualitative methodology was used to gather data for the study. A sample of 20 cases was selected purposively from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…In Uganda, for example, half of women who had been abused reported that their partner drank and one in four reported that their partner drank frequently (Koenig et al, 2003). The association between relationship violence and HIV risk is at least partly accounted for by alcohol use (Phorano, Nthomang, & Ntseane, 2005). Although it is clear that alcohol consumption and sexual violence are related, their temporal association is less clear.…”
Section: Sexual Coercionmentioning
confidence: 98%
“…In Uganda, for example, half of women who had been abused reported that their partner drank and one in four reported that their partner drank frequently (Koenig et al, 2003). The association between relationship violence and HIV risk is at least partly accounted for by alcohol use (Phorano, Nthomang, & Ntseane, 2005). Although it is clear that alcohol consumption and sexual violence are related, their temporal association is less clear.…”
Section: Sexual Coercionmentioning
confidence: 98%
“…However, in another study in the same region of Kenya, Shaffer et al 52 found no difference in the rate of hazardous alcohol consumption as defined by the WHO Alcohol Use Disorder Identification Test (AUDIT) among 299 patients (average age 39, 55% men) with and without HIV. In Botswana, Phorano et al 53 used qualitative methods to gather data from 20 participants from five women's nongovernmental organizations and conducted in-depth interviews with key informants, including social workers and police officers. They found that there was a relationship between alcohol abuse and gender-based violence, making the victims vulnerable to HIV infection.…”
Section: Alcohol Drugs and Hiv/aidsmentioning
confidence: 99%
“…In Uganda, for example, half of women who had been abused reported that their partner drank and one in four reported that their partner drank frequently (Koenig et al 2003). The association between relationship violence and HIV risk is at least partly accounted for by alcohol use (Phorano et al 2005). Although it is clear that alcohol consumption and sexual violence are related, their temporal association is less clear.…”
Section: Sexual Coercionmentioning
confidence: 97%